PERKEMBANGAN MATERI GENETIKA PADA PENGAJARAN BIOLOGI DI SMU - Suratsih, Suratsih (Jurnal Cakrawala Pendidikan, 2016)
In order to suit and respond to the develop- =ment of science and technology and other related issues, a curriculum replacement is a necessity. This curriculum analysis was carried out in order to observe the development of genetics subject matter in the curriculum of 1984 into that of 1994 and the relevance of these curricula to the anticipation of recent and future developments. Genetics was studied equally well. Analysis was conducted by comparing the curriculum of 1984 to that of 1994 and considering the development of recent and future genetics. The result shows that the genetics subject matter of the curriculum of 1984 has not shown any change; however, biotechnology as applied genetics is added to the curriculum of 1994. In conclusion, the genetics subject matter of the curriculum of 1984 is still not adequate to anticipate the development of recent and hture genetics. Addition of some related subject matter should be proposed, covering genes and gene expression, chromosomes (structure, variation of structure, variation of chromosome numbers) and cytoplasm inheritance.